A Study on the Effects of Vertical Mass Irregularity on Seismic Behavior of BRBFs and CBFs - Armin Karami (Applied Sciences, 2020)
Today, architectural application and economic constraints require that vertical-irregular structures be constructed in urban areas. Proposing methods to minimize damage to these structures during earthquakes is therefore crucial. Strict regulations have been enforced for the design and analysis of irregular structures given their higher vulnerability to damage compared to that of regular structures. The present study aimed to evaluate eight regular and irregular 10-story and 15-story steel structures with buckling-restrained braces frames (BRBFs) and concentric braced frames (CBFs) in terms of their responses to twelve far-field earthquakes. According to the obtained results, the mean value of maximum drift, top floor displacement and floor acceleration were higher in both regular and irregular structures with BRBFs than in those with CBFs.